The Character Education Based on Pancasila in the Generation Z - Wowon Winarsih; Mariatul Ulpa; Intan Sabila; Nanda Putri Amelia; Mutia Andini; Winda Agustari; Dewiana Novitasari; Madsuki Asbari; Agus Purwanto (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
The purpose of this article is to find out and describe Pancasila character education in the Era of Generation Z. Pancasila Character Education is expected to be able to form Generation Z who have the characteristics and character of good and intelligent citizens. This study uses data collection tools from articles on Google Scholar and google.com. This community service activity is carried out via zoom meeting to students from a private university in Tangerang. The conclusion of this activity is appropriate characters and shown attitudes related to the values contained in Pancasila are religious character values, social care, independence, national spirit, democracy, tolerance, and discipline. Pancasila character education is carried out by developing character education through teaching and learning activities and character education development activities through daily activities.